Clause of Unlawful Action that May Void Arbitration Rules - Ahmad Yani Kosali; Dimas Pratama Putra (Dwijendra University, 2021)
Arbitration is a way of resolving a civil dispute outside a public court based on an arbitration agreement made in writing by the disputing parties. The problem in this research is whether the Arbitration decision can be overturned by the District Court because it contains clauses of illegal acts?, and What are the forms of illegal acts that can be overturned by the District Court? The type of research used is descriptive normative legal research. From the results of the research, it can be concluded that: An Arbitration Award can be overturned by the District Court because it contains a clause on illegal acts, is a decision that has been tested and examined through a civil court hearing that it is proven based on the evidence submitted by the disputing parties that the arbitration award contains actions against the law. And a form of illegal action that can be annulled by the District Court is a decision that has permanent legal force stating that the arbitration award is proven to have been an illegal act committed by one of the parties.